The Narrative of "Marriage in Kua" on Social Media: A Narrative Analysis of Digital Cultural Practices on Platform X - Ghiffari Amrul Ramadhan; Ferry Adhi Dharma (Journal of Islamic Communication and Counseling, 2026)
Digital culture has transformed the ways individuals create, interpret, and share personal experiences, including marriage. On X (formerly Twitter), the narrative of “Marriage at the KUA” articulates a discourse centered on simplicity, efficiency, and resistance to consumerism in marital practices. This study employs a qualitative approach using narrative analysis to examine how meaning is constructed within digital cultural communication. Narrative analysis enables an exploration of how narratives are produced, circulated, and negotiated in digital spaces. Drawing on digital narrative theory, which conceptualizes social media as a space for documenting lived experiences and generating social meaning, this study finds that the “Marriage at the KUA” narrative is shaped through the affirmation of simplicity, the reinforcement of legality and religiosity, and a romanticization grounded in realistic expectations. Ultimately, this narrative has evolved into a form of digital cultural practice that fosters online communities, provides social validation, and reflects shifting marriage norms within urban digital societies.